Formulasi sediaan salep sari kelopak jantung pisang kepok (Musa paradisiaca L) terhadap penyembuhan luka sayat pada tikus putih jantan (Rattuss norvegicus) - Fahma Shufyani; Darwin Syamsul (Journal of Pharmaceutical and Sciences, 2023)
Background: Banana flower petals also have active compounds such as flavonoids, alkaloids and saponins. These active compounds are thought to be able to suppress the growth of bacteria. These compounds can be used to increase the regeneration of epidermal cells and the formation of new blood vessels to speed up healing and wound closure. This research aims to determine the healing effect of cut wounds from banana flower petals (Musa paradisiaca L) extract on male white rats (Rattus norvegicus) and what concentration is most effective in healing cut wounds. This Method research is an experimental study, including collecting samples, making kepok banana heart calyx juice with concentrations of 2%, 4% and 6%, ointment evaluation tests and cut wound healing activity tests on white mice which were grouped into 5 groups with each group consisting of of 5 mice. Statistical analysis included a one-way ANOVA test to see whether there was a significant difference between concentrations and wound healing in white male mice. The results showed that F1 (2% concentration) could heal mice on the 10th day, F2 (4% concentration) could heal mice on the 8th day, F3 (6% concentration) could heal cut wounds on the 7th day, positive control (Betadine Ointment) the mice recovered on the 6th day. The conclusion of this research is that Kepok banana heart petal juice can be formulated as an ointment for healing cuts in male white rats (Rattus norvegicus), with the most effective concentration being a concentration of 6% because it can heal cuts wounds the fastest among other concentrations.